The Influence of Individual Morality, Internal Control, Suitability of Compensation, Information Asymmetry on Accounting Fraud - Kharismatika Wijayanti; Ayu Noviani Hanum; Narcahyono, Narcahyono (Economics and Business International Conference Proceeding, 2024)
Fraud in the field of accounting has attracted a lot of public attention so that the case is no longer a secret. Many cases of accounting fraud in Indonesian banks are caused by human activities starting from human actions that lead to corruption. This study aims to examine whether there is an influence of individual morality, internal control, suitability of compensation and information asymmetry on accounting fraud at PT Bank Rakyat Indonesia Kacab A Yani Semarang. This research is a quantitative research conducted at one of the banks in Semarang City. The sample of this study amounted to 41 respondents obtained based on census / saturation techniques. Individual morality, internal control, suitability of compensation negatively affect accounting fraud. Information asymmetry positively affects accounting fraud. This research provides theoretical benefits to prove the relationship of attribution theory with individual morality, internal control, suitability of compensation, information asymmetry against accounting fraud in the banking world